Building Toward an Unmanned Aircraft System Training Strategy - Rostker, Bernard D. (RAND Corporation, 2014)
The swift adoption of unmanned aircraft systems (UASs) and their increasing use in the field have exceeded the capacity of the training infrastructure to sustain training on these systems over the long term. This report develops a general concept for training military forces in employment of UASs and a framework for addressing the training requirements and discusses the limits of existing infrastructure in supporting UAS training.